DEVELOPMENT AND QUALITY OF ‘CANTALOUPE’ MELON SEEDLINGS UNDER THE INFLUENCE OF Chlorella SP. VIA ROOT - Ana Paula Nunes Ferreira; Kilson Pinheiro Lopes; Railene Hérica Carlos Rocha Araújo; José Franciraldo de Lima; Josinaldo Lopes Araújo; Agda Malany Forte de Oliveira; Kaikí Nogueira Ferreira; Kalinny de Araújo Alves; Rita Magally Oliveira da Silva Marcelino (Revista de Agricultura Neotropical)
The search for better quality inputs with lower environmental impact has been highlighted in agricultural technology research. Microalgae can improve soil fertility and seedling development. This study aimed to evaluate the influence of suspensions as a biostimulant based on the microalgae Chlorella sp. applied via root on the production of ‘Cantaloupe’ melon seedlings. The experimental design used was completely randomized, with ten replications, in a scheme of split plots in time. The plots consisted of three concentrations (0.0, 0.8, and 1.6%) and the subplots consisted of five evaluation periods (15, 18, 21, 24, and 27 days after sowing). The treatments significantly influenced the number of leaves, total leaf area, aerial part fresh mass, root fresh mass, and total fresh mass and dry mass (p<0.01), as well as plant height and stem diameter at 5% probability level by the ‘F’ test. The concentration of 1.6% was the one that showed the best performance for the increase in leaves, plant height, total leaf area, stem diameter, and fresh and dry phytomass of melon seedlings. The most significant accumulation of fresh and dry mass in the seedlings was obtained at the concentration of 1.6% of Chlorella sp.